Comparative effectiveness of the Ilizarov method versus internal fixation for complex tibial fractures - Abu Taleb, M.; Masudur Rahman, M.; Hasan, Jahedi; Hasanusjaman, M.; Rashedul Haque, M.; Al-Habib, Hasan; Alam, Shamsul (International Journal of Research in Orthopaedics, 2026)
Background: Complex tibial fractures often occur with high-energy trauma and significant soft tissue injury. Optimal management remains controversial due to infection risks, nonunion and functional impairment. Both internal fixation and the Ilizarov method are widely used, yet comparative data in resource-limited settings remain limited. This study compared clinical, radiological and functional outcomes of the Ilizarov method versus internal fixation in complex tibial fractures. Methods: This comparative observational study was conducted in the Department of Orthopedics at 250 Bed General Hospital, Pabna and City Health Aid Hospital, Pabna, Bangladesh, from January 2024 to January 2025. A total of 30 patients with complex tibial fractures were enrolled and allocated into two groups based on the surgical intervention received. Fifteen patients underwent Ilizarov external fixation and fifteen received internal fixation. Operative parameters, union time, complications and 12-month functional outcomes were assessed. Statistical analysis was performed using statistical package for the social sciences (SPSS) version 25.0. Results: Operative time was longer in the Ilizarov group (p=0.004). Time to full weight bearing (p=0.006) and radiological union (p=0.049) were significantly shorter with Ilizarov fixation. Knee society scores (p=0.016) and Oxford knee scores (p=0.009) were significantly higher in the Ilizarov group at 12 months. Pin tract infection occurred in 26.7% of Ilizarov cases, while deep infection and nonunion were more frequent in the internal fixation group. Overall complication rates did not differ significantly. Conclusions: The Ilizarov method provided earlier rehabilitation and superior functional outcomes compared to internal fixation in complex tibial fractures.